The Effect of Digital Educational Game "Qreatif Edukatif" on the Development of Numeracy Skills in 4-5 Years Old Children - Inafazri, Siti Aisyah; Formen, Ali (Devotion : Journal of Research and Community Service, 2024)
Children's numerical skills sometimes face challenges, therefore ways are needed to maximize early childhood numeracy learning outcomes. This study aims to determine the effect of the use of digital educational games on numeracy development in children aged 4-5 years conducted in one of the Global Kindergartens (pseudonyms) in Semarang City. The method used is pre-experimental  research with a One Group Pretest-Posttest design. This participant consisted of 31 children in the Kindergarten A class. Data collection was carried out through pretest and posttest of numeracy skills developed based on the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 137 of 2014 (National Standard for Early Childhood Education). The results showed that the average pretest score  was 28.00 and the posttest increased to 46.16 after the use of  digital educational games. The normality test shows normal distributed data, while the N-Gain Score test produces an average score of 0.91 which is classified as a high category. The hypothesis test using the Paired Sample T-Test showed a Sig. (2-tailed) value of 0.000, which means that there is a significant influence of the use of  digital educational games on children's numeracy skills. This increase shows that the proper use of  digital games in learning can significantly improve early childhood numeracy skills. This study suggests the integration of digital educational games in the early childhood education curriculum as an effective alternative to improve numeracy skills.